Analisis Hubungan Budaya Perusahaan Terhadap Penerapan Good Corporate Governance Pada Cv Exim Traders Jombang - Kholifatin, Luluk Indah; Rosidah, Ani Lailatul; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This article aims to determine the relationship between the role of corporate culture and Good Corporate Governance (GCG). The research method used is a survey method and correlation techniques by distributing questionnaires with two types of instruments, namely corporate culture and GCG instruments. Respondents are permanent employees of CV. Exim Traders Jombang totaling 100 people and 87 people were selected who were determined from the formula in Suherman's book and were selected by homogeneous sampling technique in simple random sampling. Data analysis uses simple linear regression and simple correlational techniques. The results show that there is a strong correlation between corporate culture and Good Corporate Governance (GCG), meaning that the stronger the application of corporate culture, the higher the implementation of GCG.